Variation of soil and water volumes in riparian jungle soils of Brazil - Rodrigues, Valdemir Antonio [UNESP]; Moraes, Maria Helena [UNESP]; Canales, Antonio Ruiz; Rezende, Marcos Antonio [UNESP]; Costa, Vladimir Eliodoro [UNESP]; Bruder, Edson Marcelo [UNESP] (My University, 2013)
The objective of this work is to study the relation between humidity, density, porosity and shrinkage of the floodplain soil and riparian vegetation and their ability to store water. For this purpose, two locations for every type of soils were evaluated. Both were placed at the Agronomy University (Faculdade de Ciências Agronômicas) in São Manuel, State of São Paulo, Brazil. The floodplain soil was vegetated with Southern Cattail (Typha domingensis). In both places, soil samples were collected from several depths: 0, 30, 60 and 100 cm. Results show that lower soil density values (0.15 g/cm3) with organic texture and high porosities values (up to 86.2%) were found in samples with the highest organic material content in the floodplain soil. For this field experiment, flood plains soils (characterised as basin gley soils) presented high volumetric instability with a retratibility of 67.49% and higher water storage capacities compared to riparian stands soils (characterised as fluvic neosoils).
Keywords: Soil; Water; Density; Porosity; Riparian jungle